Good Citizenship Made Easy: A Step‐by‐Step Guide to Submitting RNA‐Seq Data to NCBI. Issue 1 (13th November 2018) - Feindt, Wiebke; Oppenheim, Sara J.; DeSalle, Robert; Mehr, Shaadi
Abstract: The analysis of transcriptome data from non‐model organisms contributes to our understanding of diverse aspects of evolutionary biology, including developmental processes, speciation, adaptation, and extinction. Underlying this diversity is one shared feature, the generation of enormous amounts of sequence data. Data availability requirements in most journals oblige researchers to make their raw transcriptome data publicly available, and the databases housed at the National Center for Biotechnology Information (NCBI) are a popular choice for data deposition. Unfortunately, the successful submission of raw sequences to the Sequence Read Archive (SRA) and transcriptome assemblies to the Transcriptome Shotgun Assembly (TSA) can be challenging for novice users, significantly delaying data availability and publication. Here we present two comprehensive protocols for submitting RNA‐Seq data to NCBI databases, accompanied by an easy‐to‐use website that facilitates the timely submission of data by researchers of any experience level. © 2018 by John Wiley & Sons, Inc.